PENYEMBUHAN LUKA PADA TERNAK SAPI DENGAN EXTRAK DAUN AWAR AWAR (Ficus septica Burm. F) Healing Wounds on Cattle With Awar Awar Leaf Extract (Ficus septica Burm.F) - Supriyanto, Supriyanto (UPPM Politekik Pembangunan Pertanian Yogyakarta Magelang (Polbangtan Yoma), 2017)
The wound is a form of tissue damage due to contact with sharp objects, heat, chemicals or radiation. The effects of Awar-Awar leaf extract (Ficus septica Burm.F) have been performed on topical curing of cow skin skins in order to determine the epithelial capability of Awar-Awar leaf extract (Ficus septica, Burm.F) in cattle. A total of 9 cows were injured divided into 3 groups. Three (3) treatment groups given Awar-Awar leaf extract with concentrations of 50%, 75% and 100% were topically 2 times daily. Wound Observations were performed on 3rd, 7th, 11th, 14th and 15th days. Wound evaluation was done by observing the duration of wound healing with the wound diameter reduction indicator. The results showed that Awar-Awar leaf extract at concentration 50%, 75% and 100% mean percentage (%) decrease 24,99%, 24,64% and 24% respectively. Thestatistical test obtained from Awar-Awar leaf extract has epitelisasi capability in cow and at concentration 50%, 75% and 100% not significantly different, the concentration 50% as the drug has better wound disposal ability. Keywords: extract, awar-awar leaves, healing and wounds